Kajian Total Quality Management dengan Kinerja Pegawai di Puskesmas Tuminting Kota Manado - Rumayar, Adisti A.; Warouw, Trixy Cecilia (JIKMU, 2015)
Total Quality Management merupakan pendekatan manajemen untuk memadukan upayaupaya pengembangan mutu, pemeliharaan mutu, dan peningkatan mutu dari berbagai kelompok dalam organisasi untuk menghasilkan produk yang paling ekonomis serta terpenuhinya kepuasan konsumen. Penelitian ini bertujuan untuk untuk mengetahui apakah ada hubungan antara Total Quality Management (TQM) (pendidikan dan pelatihan serta kerjasama tim (teamwork) dengan kinerja pegawai di Puskesmas Tuminting. Jenis penelitian ini adalah penelitian kuantitatif dengan pendekatan cross sectional study.Dengan melibatkan 44 responden. Data yang dapat dianalisis secara univariat dan bivariat. Data primer didapatkan dari kuisioner dan data sekunder dari Profil Puskesmas Tuminting. Uji statistik yang digunakan adalah uji chi-square. Hasil penelitian menunjukkan bahwa terdapat hubungan antara pendidikan dan pelatihan dengan kinerja pegawaiKata Kunci : Pendidikan dan Pelatihan, Kerjasama Tim, Kinerja, TQM Abstract The key to efficient and effective healthcare system is a medical worker which had competence, motivation and commitment. Nurse is one of important element in hospital management. The success of nursery is determine by the nursing performance. Nursing performance affected by a lot of factor which from the outside and also among each of the individual. The purpose of this research is to analyze the relationship between length of working with mental nursing performance in Prof. Dr. V. L. Ratumbuysang Mental Hospital. This research uses survey analytic methods with a cross sectional approach. The population on this research is all the mental nurses who worked at Prof. Dr. V. L. Ratumbuysang Mental Hospital which is as much as 92 person. Sampling methods used in this research is total sampling. Primary data obtained directly from the responden using questionnaire. The data is processed with univariate and bivariate through chi square analysis. Results of this study shows that there is relationship between length of working with nursing performance at Prof. Dr. V. L. Ratumbuysang Mental Hospital. Keywords : Length of Working, Performance